2017
DOI: 10.1002/lno.10588
|View full text |Cite
|
Sign up to set email alerts
|

Cyanate distribution and uptake in North Atlantic coastal waters

Abstract: Cyanate (OCN−) is a reduced nitrogen compound that may be a source of nitrogen and carbon for marine phytoplankton. Cyanate is produced photochemically and through organic matter degradation but its distribution in marine systems is poorly defined because, until recently, there was no method to measure its concentration in marine environments. Here, we report results from the first regional oceanographic survey of cyanate distributions and uptake. Cyanate concentrations ranged from below detection (0.4 nM) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…The concentration of a dissolved compound in seawater reflects the balance of its production and consumption, and in the ETSP, the more uniform, higher OCN − concentrations in the euphotic zone likely reflect higher rates of OCN − production in the ETSP than in the North Atlantic. OCN − uptake rates in the upper oxic layer of the ETSP (0.1 ± 0.1 nmol N L −1 h −1 ) were an order of magnitude lower than uptake rates in the North Atlantic in August (1.1 ± 1.0 nmol N L −1 h −1 ; Widner and Mulholland ), and diatoms, which are dominant in the ETSP (Pennington et al ; Franz et al ) but not in the North Atlantic in August (Pan et al ), have been shown to produce cyanate in culture (Widner et al ). The regional difference in OCN − profile shape may also reflect very different stratification and mixing regimes between the two locations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The concentration of a dissolved compound in seawater reflects the balance of its production and consumption, and in the ETSP, the more uniform, higher OCN − concentrations in the euphotic zone likely reflect higher rates of OCN − production in the ETSP than in the North Atlantic. OCN − uptake rates in the upper oxic layer of the ETSP (0.1 ± 0.1 nmol N L −1 h −1 ) were an order of magnitude lower than uptake rates in the North Atlantic in August (1.1 ± 1.0 nmol N L −1 h −1 ; Widner and Mulholland ), and diatoms, which are dominant in the ETSP (Pennington et al ; Franz et al ) but not in the North Atlantic in August (Pan et al ), have been shown to produce cyanate in culture (Widner et al ). The regional difference in OCN − profile shape may also reflect very different stratification and mixing regimes between the two locations.…”
Section: Discussionmentioning
confidence: 99%
“…OCN − concentrations in late summer (August) in the coastal North Atlantic between Cape Hatteras and the Gulf of Maine ranged from 0 nM to 25 nM (Widner et al ; Widner and Mulholland ); however, in the ETSP, OCN − concentrations were at or near the limit of analytical detection at most stations and depths measured. The North American Atlantic coastal region is an N‐limited, temperate system influenced by western boundary currents with a relatively wide continental shelf and a mixed, seasonally dynamic phytoplankton community (Townsend et al ; Pan et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations